Análisis del método FIFO y promedio ponderado para el control de inventarios para la adquisición de materia prima. - Loor Vera, Holger Emilio (My University, 2019)
The present study is an analysis of fifo and weighted average methods to the company color market, which seeks to improve the performance of inventory control that keeps in the warehouse, whose purpose is to find an appropriate method that generates a framework of profits, by means of the analysis of these two methods it will be possible to mitigate the costs by products, costs of inventory and utilities that is suitable for the company and generate an address for the decision making in the processes of purchase of the products. Inventory control is a key part of the development of a company to maintain adequate costs, which greatly depends on the type of products that the company keeps attached to the appropriate method, whether fifo or weighted average, in which the NIC2 standards establish that they are the essential for the accounting of inventories. The methodology established was cross-sectional and descriptive, which was done using the fifo and weighted average methods, measured by kardez, daily book and general ledger to manage results that allow a comparison of these methods to visualize the strengths and weaknesses that each method will maintain. in the company color market. Whose final result is to see which method is most appropriate to generate a management to make a correct decision of the accounting data management of the inventory and can maintain an optimal commercial development.
El presente trabajo de estudio se trata de un análisis de los métodos fifo y promedio ponderado a la empresa color market, cual se buscas mejorar el desempeño del control de inventario que mantiene en bodega, cuyo finalidad es buscar un método adecuado que le genere un marco de ganancias, por medio del análisis de estos dos métodos se podrá mitigar los, costos por productos, costos del inventario y utilidades que resulte idónea para la empresa y genere un direccionamiento para la toma de decisiones en los procesos de compra de los productos. El control de inventario es una pieza clave del desarrollo de una empresa por mantener los costos adecuados, cual mucho depende mucho del tipo de productos que mantiene la empresa anexada al método adecuado ya sea fifo o promedio ponderado en que las normas NIC2 establece que son las esenciales para la contabilidad de los inventarios. La metodología establecía es transversal y descriptiva cual se realizó los métodos fifo y promedio ponderado, por medido de kardez, libro diario y libro mayor para gestionar resultados que de manera permita realizar una comparación de dichos métodos para visualizar las fortalezas y debilidades que mantendrá cada método en la empresa color market. Cuyo resultado final es ver que método más adecuado que genere una gestión para toma decisión correcta del manejo de datos contables del inventario y pueda mantener un óptimo desarrollo comercial.
Keywords: CONTROL; INVENTARIO; CONTABILIDAD; OPTIMIZACIÓN; UTILIDAD; MÉTODO DE CONTROL